The Investment Attractiveness of Economic Activities in the Regions of Ukraine - Nechyporuk Oksana V. (Bìznes Inform, 2021)
The article is aimed at studying the investment attractiveness of types of economic activity in the regions of Ukraine, determining the impact of factor values (of types of economic activity) on the volume of products sold. As a result of the study, a methodical approach to the analysis and determination of investment attractiveness of types of economic activity in the regions of Ukraine is developed; the influence of factor values (of types of economic activity) on the volume of products sold is determined, the main ones are distinguished by means of correlation analysis and the significance of the selected factors of influence is checked using regression analysis. For the analysis, data was formed on the basis of official data of the State Statistics Service of Ukraine and the Ministry of Economy of Ukraine. To obtain more accurate summary results, the data was normalized in order to convert the values of signs in the input vector to a certain specified range. After the normalization, summary data for correlation and regression analysis were computed. On the basis of the carried out analysis, the economic-mathematical models of influence of investment instruments of the State budget on types of economic activity and a model of influence of investment instruments of foreign direct investment on types of economic activity in the regions of Ukraine were built. The investment attractiveness of certain regions for public investment and for foreign investments is substantiated. Prospects for further research in this direction are the analysis of the impact of other factors on the investment attractiveness of a particular region and Ukraine in general.